2020
DOI: 10.13189/ujer.2020.082545
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perception on the Use of Digital Mind Map to Stimulate Creativity and Critical Thinking in ESL Writing Course

Abstract: In practise, mind maps have long been used by individuals especially teachers to create, visualise, arrange, and expand ideas in order to facilitate teaching and learning. Learning visually is a distinctive technique in modern pedagogy because most individuals are visual learners. As technology advances, digital mind map is created to replace manual mind map to bring modern pedagogy into the era of the fourth industrial revolution. Digital mind map has been used by teachers to teach diverse subjects. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
3
12
0
1
Order By: Relevance
“…In addition, Karim and Mustapha (2020) conducted a case study to investigate the usage of digital mind map in stimulating creativity and critical thinking skills among students in writing tasks and the result of the survey indicated positive perceptions of students toward the digital mind map. The digital mind map aided them to brainstorm ideas and improved their writing skills as it helped them to organise ideas without difficulty and write efficiently.…”
Section: Studies On Perception and Attitudes In Esl Classroommentioning
confidence: 99%
“…In addition, Karim and Mustapha (2020) conducted a case study to investigate the usage of digital mind map in stimulating creativity and critical thinking skills among students in writing tasks and the result of the survey indicated positive perceptions of students toward the digital mind map. The digital mind map aided them to brainstorm ideas and improved their writing skills as it helped them to organise ideas without difficulty and write efficiently.…”
Section: Studies On Perception and Attitudes In Esl Classroommentioning
confidence: 99%
“…Pertama, persepsi adalah sebuah proses untuk merangsang interpretasi yang diterima seseorang atas dasar panca indera, pengamatan, dan pengalamannya [21]. Persepsi seseorang juga bisa dimaknai sebagai hasil perbedaan sudut pandang dan intuisi seseorang terhadap sebuah objek atau kejadian [22]. Oleh karena itu, persepsi seseorang dapat membawa pengaruh cara pandang positif ataupun negatif pada sebuah fenomena.…”
Section: Kajian Literaturunclassified
“…In terms of technology, a better quality of life could be achieved using proper and safe technologies. Furthermore, TVET students should be trained to be technological literate in line with the Fourth Industrial Revolution (IR 4.0) requirements which are primarily engaged with the use of digital technologies, artificial intelligence (AI) and big data Karim & Mustapha, 2020). One of the goals of the digital revolution is to build resilient and competent digital talent to create an inclusive digital society (The Edge Malaysia, 2020).…”
mentioning
confidence: 99%
“…Based on their empirical research, Wijayanti et al (2020) found that students' communication skills improved by using mind mapping. Regarding the learning tools that the TVET students need to master, the digital mind map is one of them (Karim & Mustapha, 2020). Buzan (2009) describes mind mapping as a technique of storing, editing, and organising information by means of using keywords and key images.…”
mentioning
confidence: 99%
See 1 more Smart Citation